2022
DOI: 10.1038/s41537-022-00313-0
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and availability of smartphone apps for schizophrenia

Abstract: App-based interventions have the potential to enhance access to and quality of care for patients with schizophrenia. However, less is known about the current state of schizophrenia apps in research and how those translate to publicly available apps. This study, therefore, aimed to review schizophrenia apps offered on marketplaces and research literature with a focus on accessibility and availability. A search of recent reviews, gray literature, PubMed, and Google Scholar was conducted in August 2022. A search … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 141 publications
0
7
0
Order By: Relevance
“…However, there is also a lack of consensus or standards for assessing and monitoring engagement with and attrition from digital tools, limiting progress in the field [ 39 ]. In addition, most of the research on and development of digital tools focuses on conditions outside SMI [ 11 ]. Digital technologies, particularly smartphone apps, have the potential to be novel tools for managing SMIs, especially in LMICs [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is also a lack of consensus or standards for assessing and monitoring engagement with and attrition from digital tools, limiting progress in the field [ 39 ]. In addition, most of the research on and development of digital tools focuses on conditions outside SMI [ 11 ]. Digital technologies, particularly smartphone apps, have the potential to be novel tools for managing SMIs, especially in LMICs [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This will involve a comprehensive analysis of implementation costs, integration into the existing IT infrastructures of the institution, and regulatory and privacy compliance, but this may not have been adequately assessed at the beginning of the process. A result is that many digital health technologies are not iterated and sustained, with a 2022 review finding that nearly half of apps created for schizophrenia research in the last decade are no longer accessible or supported [ 11 ]. These challenges in funding impede replication and impair the research-to-clinical translation of digital mental health tools (see further discussion in theme 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to note that although this review identified a total of nine digital smoking cessations trialed in SMI, only two of these ( QuitGuide and quitStart ) are readily available online, which showed poorer results in terms of effectiveness and have not been assessed as thoroughly as mSMART MIND and iCOMMIT for acceptability and safety. The general inaccessibility of evidence-based digital interventions for SMI is a problem which extends far beyond smoking cessation, with a recent review finding that only ~15% of apps trialing in schizophrenia are currently available online (Kwon, Firth, Joshi, & Torous, 2022 ). Clearly, further work is needed to improve the dissemination of effective digital approaches into the public sphere more generally.…”
Section: Discussionmentioning
confidence: 99%